Effect of recycled aggregate and steel fiber contents on the mechanical properties and sustainability aspects of alkali-activated slag-based concrete. (1st May 2023) - Li, Biao; Yu, Shiting; Gao, Benhao; Li, Yang; Wu, Fanghong; Xia, Dongtao; Chi, Yin; Wang, Songbo
Abstract: Using industrial solid waste to substitute cement and recycled concrete aggregate (RA) to replace natural aggregate (NA) in concrete is seemed as an effective approach to control the global warming and save resources in construction and building engineering. This paper investigates the effect of RA and steel fiber (SF) contents on the mechanical properties of alkali-activated slag-based concrete (AAC). Three SF volume fractions of 0.5%, 1.0% and 1.5%, four RA replacement levels of 25%, 50%, 75% and 100% are considered. The mechanical properties of failure mode, compressive and splitting tensile strength, flexural behavior as well as carbon emission and cost are studied. The results indicate the inclusion of RA weakens the compressive and splitting tensile strengths as well as flexural behavior of AAC, especially for peak load, deflection and toughness. The addition of SF has a limited effect on the compressive strength but significantly enhances the splitting tensile strength and flexural behavior. Moreover, negative synergy of RA and SF is found for the compressive and splitting tensile strength, whereas it shows a notable positive synergy for flexural properties. Results from life cycle assessment show that AAC with 100% and 0% RA have 67.17% and 48% carbon emission reduction compared to plain concrete, respectively. From the present study, the optimal levels are 0.5% for SF volume fraction and 50% for RA content. Highlights: Effect of RA and SF contents on mechanical properties of alkali-activated concrete was studied. The failure mechanism of AARAC and synergy of RA and SF were discussed. The carbon emission and unit cost of AAC were analyzed using a LCA method.